2018
DOI: 10.1007/s00246-018-1807-x
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Valve Morphology in Patients with Bicuspid Aortic Valves

Abstract: The aortic and pulmonary valve share a common developmental origin from the embryonic arterial trunk. Bicuspid aortic valve is the most common congenital anomaly and can occur isolated as well as in association with other congenital heart disease (CHD). Data on pulmonary valve morphology in these cases are scarce. In this study, we aimed to determine pulmonary valve morphology in hearts with BAV associated with CHD. In 83 post-mortem heart specimens with BAV and associated CHD, pulmonary valve morphology was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The pulmonary valve is morphologically similar to the aortic valve, [32][33][34] but also has differences, such as lack of a defined fibrous annulus. In addition, it is wedged between the aortic semilunar valve and the ventricular myocardium, all of which lend support.…”
Section: Discussionmentioning
confidence: 99%
“…The pulmonary valve is morphologically similar to the aortic valve, [32][33][34] but also has differences, such as lack of a defined fibrous annulus. In addition, it is wedged between the aortic semilunar valve and the ventricular myocardium, all of which lend support.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Koenraadt et al [ 120 ] suggested that absence of raphe was represented in 25% of Dutch patients with BAV. Moreover, in cases of BPV, the majority also had BAV without raphe, suggesting that whatever process causes bicuspid valves without raphe, it affects both valves at the same time [ 139 ]. However, it should be remembered that a raphe might be present initially and then disappear later, particularly if the fusion event occurred very early in development [ 125 ].…”
Section: Bicuspid Valve Without Raphe and The Absent Leafletmentioning
confidence: 99%